Systematic protein–protein interaction mapping for clinically relevant human GPCRs - Kate Sokolina; Saranya Kittanakom; Jamie Snider; Max Kotlyar; Pascal Maurice; Jorge Gandía; Abla Benleulmi‐Chaachoua; Kenjiro Tadagaki; Atsuro Oishi; Victoria Wong; Ramy H Malty; Viktor Deineko; et al. (Molecular Systems Biology)
Abstract G‐protein‐coupled receptors (GPCRs) are the largest family of integral membrane receptors with key roles in regulating signaling pathways targeted by therapeutics, but are difficult to study using existing proteomics technologies due to their complex biochemical features. To obtain a global view of GPCR‐mediated signaling and to identify novel components of their pathways, we used a modified membrane yeast two‐hybrid (MYTH) approach and identified interacting partners for 48 selected full‐length human ligand‐unoccupied GPCRs in their native membrane environment. The resulting GPCR interactome connects 686 proteins by 987 unique interactions, including 299 membrane proteins involved in a diverse range of cellular functions. To demonstrate the biological relevance of the GPCR interactome, we validated novel interactions of the GPR37, serotonin 5‐HT4d, and adenosine ADORA2A receptors. Our data represent the first large‐scale interactome mapping for human GPCRs and provide a valuable resource for the analysis of signaling pathways involving this druggable family of integral membrane proteins.